Assessment of the neuroprotective potential of d-cycloserine and l-serine in aluminum chloride-induced experimental models of Alzheimer’s disease: In vivo and in vitro studies - Tozlu, Özlem Özdemir; Türkez, Hasan; Okkay, Ufuk; Ceylan, Onur; Bayram, Cemil; Hacımüftüoğlu, Ahmet; Mardinoğlu, Adil (Frontiers in Nutrition, 2022)
Alzheimer's disease (AD) is a neurodegenerative disease characterized by the accumulation of amyloid-β (Aβ) plaques and neurofibrillary tangles in the brain accompanied by synaptic dysfunction and neurodegeneration. No effective treatment has been found to slow the progression of the disease. Therapeutic studies using experimental animal models have therefore become very important. The potential effects of D-cycloserine and L-serine in the AlCl3-induced experimental rat model of AD were determined by behavioral tests, pathological examination, biochemical and hematological evaluation and molecular genetic analyses. In this study, 6 groups of female Sprague–Dawley rats were used: Group 1, control group (n = 5); Group 2, experimental AD group with administration of AlCl3 (n = 5); Group 3, D-cycloserine group (only D-cycloserine n = 5); Group 4, L-serine group (only L-serine n = 5); Group 5, treatment with D-cycloserine (n = 5); and Group 6, treatment with L-serine (n = 5). Oxidative stress and neurodegeneration were observed in an AlCl3-induced experimental rat model of AD, and the experimental Alzheimer’s disease rat model was confirmed by behavioral tests. In addition, we found that aluminum decreases α-secretase activity while increasing β-secretase and γ-secretase activities by molecular genetic analysis. D-cycloserine and L-serine application resulted in an improvement in neurodegeneration and oxidative damage caused by aluminum toxicity. It is believed that the results of this study will contribute to the synthesis of new compounds with improved potential against AlCl3-induced neurodegeneration and cognitive impairment and to drug development research.